PENYELESAIAN SOLITON PADA PERSAMAAN GELOMBANG - Nugroho, Gunawan (Jurnal Teknik Kimia, 2007)
The wave equation is reviewed in this research. Soliton solution of wave equation can begenerated by two constrains according to spatial dispersion. Method that used in current investigation isperiodic solution of wave equation transformed to soliton by utilizing power series. The results are thengeneralized. One dimesional analysis shows that the constrains is trivially fulfilled, but two and threedimensional studies show that nonlinear term is appeared, therefore the problems are not easily solved.Keywords : Wave equation, soliton, dispersion